The Influence of GDP, Coal Exports, and Fossil Energy Consumption On Indonesian Air Pollution Reviewed From CO2 Emissions - Ester Valentine Yakin; I Made Endra Kartika Yudha (International Journal of Management Research and Economics, 2024)
Air is very vital for the survival of living things, therefore it is important to maintain air quality to avoid pollution. One of the causes of air pollution is high carbon dioxide emissions resulting from economic and industrial activities which are trapped in the atmosphere, causing a greenhouse gas effect. This research aims to determine the influence of GDP, coal exports and fossil energy consumption on air pollution in Indonesia in terms of CO 2 emissions . This research also aims to test whether the Environmental Kuznet Curve (EKC) hypothesis applies in Indonesia. The type of data used in this research is secondary data in the form of quantitative data obtained from BPS, World Bank, etc. This research was conducted in all provinces in Indonesia. The data analysis technique used in this research is the Error Correction Model ( ECM). The research results show that in the short and long term the variables GDP, coal exports and energy consumption simultaneously have a significant effect on the level of CO 2 emissions . GDP in the short term and long term does not partially have a significant effect on the level of CO 2 emissions . Meanwhile, GDP squared in the short term partially has no significant effect and in the long term it partially has a positive and significant effect. This shows that the EKC hypothesis does not apply in Indonesia. Coal exports in the short term and long term partially do not have a significant effect. Fossil energy consumption in the short term and long term partially has a positive and significant effect. Considering the importance of air for human life, it is necessary to pay attention to the factors that influence air pollution.